A uranium adsorption material composited with electric field-assisted cyanation MOFs and graphene aerogel and a preparation method thereof
Through the preparation of electric field-assisted cyanolated MOFs and graphene aerogel composite materials, the problem of low adsorption efficiency of existing adsorbents on hexavalent uranium is solved, and uranium is efficient and selectively enriched in seawater, and the material is environmentally friendly and resilient.
Patent Information
- Application Number
- CN202411056756.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-08-02
AI Technical Summary
The existing adsorbents have a long time to enrich hexavalent uranium in water bodies and have low adsorption efficiency, making it difficult to meet the efficient extraction needs of uranium resources in seawater.
The electric field-assisted cyanolated MOFs and graphene aerogel composite is prepared by solvent-thermal reaction and hydrothermal reaction, combined with electric field-assisted technology to improve uranium adsorption performance.
Highly efficient adsorption and selective enrichment of hexavalent uranium is achieved, which can maintain excellent selectivity in seawater with extremely low uranium concentration and complex composition, and the material is environmentally friendly and recyclable.
Smart Images

Figure CN118904304B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of chemistry and environmental technology, and in particular to an electric field-assisted cyanated MOFs and graphene aerogel composite uranium adsorption material and a preparation method thereof. Background Art
[0002] As an efficient, clean and economical energy source, nuclear energy can not only provide safe and stable energy, but also bring huge economic benefits to human society and reduce air pollution, which has attracted worldwide attention. However, as one of the most important fuels for nuclear reactors, the limited uranium reserves in terrestrial ores may be exhausted within a century. Fortunately, the amount of uranium resources in the ocean is estimated to be about 4.5 billion tons, showing abundant uranium resources. If the uranium resources in the ocean can be extracted and utilized, sustainable nuclear energy production will be possible for at least 1,000 years. Therefore, extracting uranium from seawater is considered to be the most promising way to overcome the shortage of terrestrial uranium resources and achieve sustainable nuclear energy production.
[0003] Due to the ultra-low concentration (~3.3ppb), extremely high salinity and abnormally high abundance of interfering ions in seawater, it is extremely challenging to recover uranium from seawater. To date, a variety of strategies have been applied to the extraction of metal ions from seawater, such as electrochemical extraction, adsorption, photocatalytic reduction, membrane separation, ion exchange and other methods. Compared with other methods, adsorption has become one of the most effective and environmentally friendly methods for extracting metal ions due to its significant effects, simple operation, green environmental protection, and large-scale production.
[0004] Metal organic frameworks (MOFs), as a class of porous crystalline materials composed of metal nodes and organic ligands, have attracted widespread attention. MOFs have played a vital role in the development of new uranium adsorbents due to their high specific surface area, high porosity, highly ordered pore structure, abundant active sites and adjustable pore structure. Graphene aerogel (GA) has a three-dimensional continuous porous network structure, which inherits the advantages of graphene and aerogel, such as high conductivity, high specific surface area, high porosity and good mechanical strength, and has been widely used in recent years.
[0005] In view of the problem that existing adsorbents take a long time to enrich hexavalent uranium in water and have low adsorption efficiency, there is an urgent need to develop uranium enrichment composite materials with high adsorption capacity, stable structure and repeated reuse. Summary of the invention
[0006] The purpose of the present invention is to provide an electric field assisted cyanated MOFs and graphene aerogel composite uranium adsorption material and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art and achieve efficient adsorption and removal of uranium.
[0007] To achieve the above object, the present invention provides the following solutions:
[0008] One of the technical solutions of the present invention is to provide a method for preparing an electric field-assisted uranium adsorption composite material, the steps comprising:
[0009] A metal ion-containing salt and an organic ligand are used as reactants, and a MOFs material containing a cyano group is obtained through a solvent thermal reaction; the organic ligand is terephthalic acid and 2,5-dicyanoterephthalic acid;
[0010] Graphene oxide and carboxylated cellulose nanofibers are used as reactants, ethylenediamine is used as a cross-linking agent, and a graphene aerogel (GA) is obtained through a hydrothermal reaction.
[0011] The MOFs material containing cyano groups and GA are mixed and loaded in a solvent, and then dried to obtain the electric field assisted uranium adsorption composite material.
[0012] Furthermore, the molar ratio of the metal ion to the organic ligand in the metal ion-containing salt is 1:1-10.
[0013] Furthermore, the metal ions in the metal ion-containing salt include Zr 4+ , Fe 3+ , Cu 2+ and Zn 2+ At least one of .
[0014] Furthermore, the molar ratio of terephthalic acid to 2,5-dicyanoterephthalic acid is 1:0.2-5.
[0015] Furthermore, the temperature of the solvent thermal reaction is 120° C. and the time is 12 to 48 hours.
[0016] Furthermore, the mass ratio of the graphene oxide to the carboxylated cellulose nanofibers is 1:0.1-1.
[0017] Furthermore, the mass / volume ratio of the sum of the masses of the graphene oxide and the carboxylated cellulose nanofibers to ethylenediamine is 0.055-0.1 g:2 μL.
[0018] Furthermore, the temperature of the hydrothermal reaction is 120° C., and the time is 8 to 12 hours.
[0019] Furthermore, the mass ratio of the MOFs material containing cyano groups to the graphene aerogel is 1:1 to 12.5.
[0020] Furthermore, the mixing reaction is carried out for 24 to 48 hours at room temperature.
[0021] Furthermore, the solvent is N,N-dimethylformamide.
[0022] The second technical solution of the present invention is to provide an electric field assisted uranium adsorption composite material prepared by the above preparation method.
[0023] The third technical solution of the present invention is to provide an application of the above-mentioned electric field assisted uranium adsorption composite material in uranium adsorption.
[0024] Furthermore, the application method is: adding the electric field assisted uranium adsorption composite material into water (uranium concentration is 25-200 mg / L) to adsorb and enrich hexavalent uranium, the adsorption time is 5-1440 minutes, the amount of adsorption material added is 20 mg-200 mg per liter of water, and the pH of the water is 3-10.
[0025] Technical solution 4 of the present invention: provides a uranium adsorption electrode, the raw materials of which include the above-mentioned electric field assisted uranium adsorption composite material.
[0026] A fifth technical solution of the present invention is to provide a method for preparing the above-mentioned uranium adsorption electrode, the steps comprising:
[0027] The electric field assisted uranium adsorption composite material is dispersed in an ethanol solution, and then naphthol is added, mixed evenly, and then coated on a conductive substrate to obtain the uranium adsorption electrode.
[0028] Furthermore, the mass fraction of the ethanol solution is 75-95%.
[0029] Furthermore, the volume ratio of the ethanol solution to naphthol is 40-80:1.
[0030] Furthermore, the content of the electric field assisted uranium adsorption composite material in the uniformly mixed system is 0.2-1 g:50 mL.
[0031] Furthermore, the conductive substrate is carbon paper, carbon cloth or graphite felt.
[0032] Furthermore, the loading amount of the electric field assisted uranium adsorption composite material in the uranium adsorption electrode is 0.2-2 mg / cm 2 .
[0033] Technical solution six of the present invention: provide an application of the above-mentioned uranium adsorption electrode as an adsorption material in the electro-adsorption enrichment of uranium.
[0034] Furthermore, the application method is: using the uranium adsorption electrode as a working electrode, a platinum electrode as a counter electrode, and Ag / AgCl as a reference electrode to form a three-electrode system, applying voltage to the water body (uranium concentration is 25-100 mg / L) to electro-adsorb and enrich uranium, the voltage is 0-1.2V, the pH of the water body is 3-10, the adsorption time is 5-1440min, and the adsorption temperature is 25°C.
[0035] The present invention discloses the following technical effects:
[0036] The cyano group in the electric field-assisted uranium adsorption composite material of the present invention has a strong complexing effect on uranyl ions, which can effectively increase the adsorption effect of the adsorbent material on uranyl ions. Metal ions cross-link with oxygen in carboxyl groups to form porous MOFs materials, which can increase porosity and increase active sites, thereby improving its adsorption performance. By combining the porous MOFs material with graphene aerogel, the aggregation of the MOFs material is effectively weakened, the utilization of adsorption sites is improved, and the adsorption performance of uranium is greatly improved. The adsorbent material prepared by the present invention has abundant cyano groups, has adsorption selectivity for hexavalent uranium, and can also preferentially select uranium for adsorption when other ions coexist.
[0037] The present invention aims to solve the problems that existing MOFs materials are easy to aggregate, have low adsorption capacity for hexavalent uranium, have low selectivity, and cannot adapt to seawater with complex composition. The present invention provides an electric field-assisted cyanation MOFs and graphene aerogel (GA) composite uranium adsorption material. The adsorption material has excellent adsorption selectivity for hexavalent uranium and still has excellent selectivity even under seawater conditions with extremely low uranium concentration and complex composition. The product is environmentally friendly and can be recycled.
[0038] The raw materials used in the present invention are environmentally friendly, non-toxic and harmless, and a high-performance adsorption material can be prepared by a simple method. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1 The SEM images of UiO-66-CN@GA prepared in Example 1 at different magnifications, where a is a low magnification and b is a high magnification;
[0041] Figure 2 The SEM images of the uranium adsorption electrodes prepared in Example 12 and Comparative Examples 3 to 4, wherein a is Comparative Example 2, b is Comparative Example 1, c is a low magnification of Example 12, and d is a high magnification of Example 12;
[0042] Figure 3 X-ray diffraction patterns of UiO-66-CN@GA prepared in Example 1, GA prepared in Comparative Example 1, and UiO-66-CN prepared in Comparative Example 2;
[0043] Figure 4The infrared spectra of UiO-66-CN@GA prepared in Example 1, GA prepared in Comparative Example 1, and UiO-66-CN prepared in Comparative Example 2;
[0044] Figure 5 This is a graph showing the adsorption performance of hexavalent uranium by the materials prepared in Example 1, Example 6, Example 7, Example 8 and Comparative Example 1;
[0045] Figure 6 This is a graph showing the adsorption performance of hexavalent uranium by the uranium adsorption electrode prepared in Example 12 at different voltages;
[0046] Figure 7 This is a graph showing the variation of the adsorption amount of hexavalent uranium at a voltage of 1.2 V versus adsorption time of the uranium adsorption electrode prepared in Example 12;
[0047] Figure 8 This is a graph showing the cycle regeneration performance of the uranium adsorption electrode prepared in Example 12 during the electrosorption process;
[0048] Fig. 9 This is a comparison diagram of the selective electrosorption of different metal elements by the uranium adsorption electrode prepared in Example 12;
[0049] Fig.10 It is a comparison chart of the adsorption effect of Example 1 and Example 12 on hexavalent uranium. DETAILED DESCRIPTION
[0050] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0051] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0052] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0053] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0054] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0055] Example 1
[0056] The preparation steps of the electric field assisted uranium adsorption composite material are as follows:
[0057] S1. Add 0.20 g ZrCl to 10 mL N,N-dimethylformamide. 4 (0.86mmol) and 4mL glacial acetic acid, ultrasonic for 10min, recorded as A 1 ;
[0058] S2. Add 0.0929 g 2,5-dicyanoterephthalic acid (0.43 mmol) and 0.0714 g terephthalic acid (0.43 mmol) to another 10 mL N,N-dimethylformamide and perform ultrasonication for 10 min. 2 ;
[0059] S3, A 2 Pour A 1 In the reaction mixture, ultrasonic treatment was performed for 20 minutes, and then the mixture was heated at 120°C in a hydrothermal reactor for 24 hours. After cooling to room temperature, the mixture was washed twice with 40 mL of a 1:1 DMF and ethanol mixed solution. The solid was collected and dried in an oven at 60°C for 12 hours to obtain UiO-66-CN.
[0060] S4, adding 0.05 g of graphene oxide to 5 mL of water, and ultrasonicating for 1.5 h to obtain a dispersion;
[0061] S5, add 0.005g carboxylated cellulose nanofibers to 5mL water, stir for 1h, then add the dispersion in S4, mix and stir for 30min, then add 10μL ethylenediamine, continue stirring for 15min, then hydrothermally react at 120℃ for 8h, cool to room temperature, soak in 100mL 15% ethanol solution for 24h, change the solution once in the middle, then put in a refrigerator to freeze for 24h, and finally put in a freeze drying oven to dry for 72h to obtain graphene aerogel (GA);
[0062] S6. Add 2.5 mg GA and 1 mg UiO-66-CN to 10 mL N,N-dimethylformamide, shake on a shaker at room temperature for 24 h, and then dry in a vacuum drying oven at 60 °C to obtain an electric field-assisted uranium adsorption composite material, recorded as UiO-66-CN@GA.
[0063] Example 2
[0064] Compared with Example 1, the only difference is that the molar ratio of 2,5-dicyanoterephthalic acid to terephthalic acid is 1:4, and the amounts used are 0.0372 g and 0.1143 g, respectively.
[0065] Example 3
[0066] Compared with Example 1, the only difference is that the molar ratio of 2,5-dicyanoterephthalic acid to terephthalic acid is 2:1, and the amounts used are 0.124 g and 0.047 g respectively.
[0067] Example 4
[0068] Compared with Example 1, the only difference is that the molar ratio of 2,5-dicyanoterephthalic acid to terephthalic acid is 2:3, and the amounts used are 0.074 g and 0.028 g, respectively.
[0069] Example 5
[0070] Compared with Example 1, the only difference is that the mass ratio of graphene oxide to carboxylated cellulose nanofibers is 5:1, and the amounts used are 0.05 g and 0.01 g, respectively.
[0071] Example 6
[0072] Compared with Example 1, the only difference is that the mass ratio of graphene aerogel to UiO-66-CN is 1:1, and the amounts used are 2.5 mg and 2.5 mg respectively.
[0073] Example 7
[0074] Compared with Example 1, the only difference is that the mass ratio of graphene aerogel to UiO-66-CN is 5:1, and the amounts used are 2.5 mg and 0.5 mg respectively.
[0075] Example 8
[0076] Compared with Example 1, the only difference is that the mass ratio of graphene aerogel to UiO-66-CN is 12.5:1, and the amounts used are 2.5 mg and 0.2 mg respectively.
[0077] Example 9
[0078] Compared with Example 1, the only difference is that the metal ions are provided by zinc chloride, and the molar amount of the metal ions is the same.
[0079] Example 10
[0080] Compared with Example 1, the only difference is that the metal ions are provided by ferric chloride, and the molar amount of the metal ions is the same.
[0081] Embodiment 11
[0082] Compared with Example 1, the only difference is that the metal ions are provided by cupric chloride, and the molar amount of the metal ions is the same.
[0083] Example 12
[0084] The preparation steps of uranium adsorption electrode are as follows:
[0085] The UiO-66-CN@GA (0.2 mg) prepared in Example 1 was dispersed in 75% ethanol, and then Nafion was added. The volume ratio of 75% ethanol to Nafion was 50:1, and the total amount was 50 μL. After mixing evenly, it was coated on the surface of carbon paper (10 mm×10 mm). After drying at room temperature for 24 h, a uranium adsorption electrode (UiO-66-CN@GA content was 0.2 mg) was obtained.
[0086] Embodiment 13
[0087] Compared with Example 12, the difference is that the amount of UiO-66-CN@GA used is 0.5 mg, and the content of UiO-66-CN@GA in the uranium adsorption electrode is 0.5 mg.
[0088] Embodiment 14
[0089] Compared with Example 12, the difference is that the amount of UiO-66-CN@GA used is 1 mg, and the content of UiO-66-CN@GA in the uranium adsorption electrode is 1 mg.
[0090] Embodiment 15
[0091] Compared with Example 12, the difference is that the amount of UiO-66-CN@GA used is 1.5 mg, and the content of UiO-66-CN@GA in the uranium adsorption electrode is 1.5 mg.
[0092] Example 16
[0093] Compared with Example 12, the only difference is that the UiO-66-CN@GA prepared in Example 1 is replaced by an equal amount of the electric field-assisted uranium adsorption composite material prepared in Example 9.
[0094] Embodiment 17
[0095] Compared with Example 12, the only difference is that the UiO-66-CN@GA prepared in Example 1 is replaced by an equal amount of the electric field-assisted uranium adsorption composite material prepared in Example 10.
[0096] Comparative Example 1
[0097] The preparation steps of porous graphene aerogel GA are as follows:
[0098] S1. Add 0.05 g of graphene oxide to 5 mL of water and sonicate for 1.5 h to obtain a dispersion;
[0099] S2, add 0.005g carboxylated cellulose nanofibers to 5mL water, stir for 1h, then add the dispersion in S4, mix and stir for 30min, then add 10μL ethylenediamine, continue stirring for 15min, then hydrothermally react at 120℃ for 8h, cool to room temperature, soak in 100mL 15% ethanol solution for 24h, change the solution once in the middle, then put it in the refrigerator to freeze for 24 hours, and finally put it in a freeze drying oven to dry for 72h to obtain porous graphene aerogel (GA).
[0100] Comparative Example 2
[0101] The preparation steps of MOFs UiO-66-CN material with high stability are:
[0102] S1. Add 0.20 g ZrCl to 10 mL N,N-dimethylformamide. 4 (0.86mmol) and 4mL glacial acetic acid, ultrasonic for 10min, recorded as A 1 ;
[0103] S2. Add 0.0929 g 2,5-dicyanoterephthalic acid (0.43 mmol) and 0.0714 g terephthalic acid (0.43 mmol) to another 10 mL N,N-dimethylformamide and perform ultrasonication for 10 min. 2 ;
[0104] S3, A 2 Pour A 1 The reaction mixture was ultrasonicated for 20 minutes and then heated at 120 °C in a hydrothermal reactor for 24 hours. After cooling to room temperature, the mixture was washed twice with 40 mL of a 1:1 mixed solution of DMF and ethanol. The solid was collected and dried in an oven at 60 °C for 12 hours to obtain a highly stable MOFs UiO-66-CN material.
[0105] Comparative Example 3
[0106] The preparation steps of uranium adsorption electrode are as follows:
[0107] The porous graphene aerogel (GA) (0.2 mg) prepared in Comparative Example 1 was dispersed in 75% ethanol, and then Nafion was added. The volume ratio of 75% ethanol to Nafion was 50:1, and the total amount was 50 μL. After mixing evenly, it was coated on the surface of carbon paper (10 mm×10 mm). After drying at room temperature for 24 h, a uranium adsorption electrode (GA content was 0.2 mg) was obtained.
[0108] Comparative Example 4
[0109] The preparation steps of uranium adsorption electrode are as follows:
[0110] The MOFs UiO-66-CN material (0.2 mg) prepared in Comparative Example 1 was dispersed in 75% ethanol, and then Nafion was added. The volume ratio of 75% ethanol to Nafion was 50:1, and the total amount was 50 μL. After mixing evenly, it was coated on the surface of carbon paper (10 mm×10 mm). After drying at room temperature for 24 h, a uranium adsorption electrode (MOFs UiO-66-CN material content was 0.2 mg) was obtained.
[0111] Test example
[0112] Figure 1 The SEM images of UiO-66-CN@GA prepared in Example 1 at different magnifications, where a is a low magnification and b is a high magnification. Figure 1 It can be seen that UiO-66-CN@GA presents a porous structure and UiO-66-CN is evenly dispersed on the surface of graphene aerogel.
[0113] Figure 2 The SEM images of the uranium adsorption electrodes prepared in Example 12 and Comparative Examples 3-4, wherein a is Comparative Example 4, b is Comparative Example 3, c is a low magnification of Example 12, and d is a high magnification of Example 12. Figure 2 It can be seen that UiO-66-CN presents a typical octahedral configuration and GA has a porous structure. Mixing UiO-66-CN with GA effectively alleviates the aggregation of UiO-66-CN and improves the utilization of adsorption sites. In addition, the uranium adsorption electrode maintains the original porous configuration of GA, which promotes the transmission of uranyl ions.
[0114] Figure 3 The X-ray diffraction patterns of UiO-66-CN@GA prepared in Example 1, GA prepared in Comparative Example 1, and UiO-66-CN prepared in Comparative Example 2 are shown in FIG. Figure 3 It can be seen that UiO-66-CN was successfully synthesized, and the spectrum of UiO-66-CN@GA showed that UiO-66-CN was successfully combined with GA.
[0115] Figure 4The infrared spectra of UiO-66-CN@GA prepared in Example 1, GA prepared in Comparative Example 1 and UiO-66-CN prepared in Comparative Example 2 are shown in FIG. Figure 4 It can be seen that there is a characteristic peak of UiO-66-CN in UiO-66-CN@GA, indicating that UiO-66-CN is successfully combined with graphene aerogel. Through the test, an obvious cyano peak can be found, indicating that the ligand is successfully combined.
[0116] The materials prepared in Example 1, Example 6, Example 7, Example 8 and Comparative Example 1 were subjected to adsorption tests. The results are as follows: Figure 5 As shown,
[0117] Adsorption test steps: add the electric field assisted uranium adsorption composite material into the water body (uranium concentration is 50 mg / L) to adsorb and enrich hexavalent uranium, the adsorption time is 5 to 1440 minutes, the amount of adsorption material added is 20 mg to 200 mg per liter of water, and the pH of the water body is 3 to 10.
[0118] Figure 5 The following is a graph showing the adsorption performance of hexavalent uranium by the materials prepared in Example 1, Example 6, Example 7, Example 8 and Comparative Example 1. Figure 5 It can be seen that Example 1 has a uranium adsorption capacity of about 300 mg / g, and has excellent physical and chemical adsorption performance.
[0119] The uranium adsorption electrode prepared in Example 12 was subjected to uranium adsorption experiments under different voltages, the steps being: using the uranium adsorption electrode as the working electrode, the platinum electrode as the counter electrode, and Ag / AgCl as the reference electrode to form a three-electrode system, applying voltage to electro-adsorb and enrich uranium in water (uranium concentration of 100 mg / L), the voltage being 0-1.2 V, the pH of the water being 3-10, the adsorption time being 5-1440 min, and the adsorption temperature being 25°C. The results are as follows Figure 6 shown.
[0120] Figure 6 The adsorption performance of the uranium adsorption electrode prepared in Example 12 for hexavalent uranium at different voltages is shown in FIG. Figure 6 It can be seen that the adsorption performance improves significantly with the increase of voltage.
[0121] The uranium adsorption experiment was carried out on the uranium adsorption electrode prepared in Example 12, and the steps were as follows: using the uranium adsorption electrode as the working electrode, the platinum electrode as the counter electrode, and Ag / AgCl as the reference electrode to form a three-electrode system, applying voltage to the water body (uranium concentration is 25-100 mg / L) to electro-adsorb and enrich uranium, the voltage is 1.2V, the pH of the water body is 3-10, the adsorption time is 5-1440min, and the adsorption temperature is 25°C. The results are as follows Figure 7 shown.
[0122] Figure 7 The graph of the adsorption amount of hexavalent uranium by the uranium adsorption electrode prepared in Example 12 under the voltage condition of 1.2V versus adsorption time is shown in FIG. Figure 7 It can be seen that at a voltage of 1.2 V, the uranium adsorption amount of more than 2000 mg / g can be reached within 1.5 h, which has excellent electrical adsorption performance.
[0123] The uranium adsorption electrode prepared in Example 12 was subjected to a cyclic regeneration experiment to determine the adsorption effect of hexavalent uranium after 10 cyclic regenerations. The experimental steps were to conduct an adsorption experiment in a 100 mg / L uranium solution with a voltage of 1.2 V for 6 h. After the adsorption was completed, a reverse voltage desorption experiment was conducted with 1 M NaCl for 3 h. After the desorption was completed, it was washed with clean water and dried at room temperature. The cycle was repeated ten times to determine the adsorption amount. The results are shown in the figure. Figure 8 shown.
[0124] Figure 8 The cyclic regeneration performance diagram of the uranium adsorption electrode prepared in Example 12 is shown in FIG. Figure 8 It can be seen that the uranium adsorption electrode of Example 12 still has a high adsorption capacity after 10 cycles of regeneration, indicating that the electric field-assisted uranium adsorption composite material of the present invention has stable performance and high reuse rate.
[0125] The uranium adsorption electrode prepared in Example 12 was subjected to a multi-metal ion coexistence adsorption experiment to determine its adsorption effect on different metal elements. The experimental steps were to conduct an electrosorption test in a 1L mixed solution containing 300 μg / L of U, V, Ba, Cu, Fe, Mg, and Na. The adsorption voltage was 1.2V and the adsorption time was 24h. After the adsorption was completed, the concentration of each ion before and after adsorption was determined to calculate the adsorption amount. The results are shown in Figure 1. Fig. 9 shown.
[0126] Fig. 9 This is a comparison diagram of the selective electrosorption of different metal elements by the uranium adsorption electrode prepared in Example 12. Fig. 9 It can be seen that the uranium adsorption electrode prepared by the present invention has excellent selectivity for hexavalent uranium.
[0127] The electric field assisted uranium adsorption composite material prepared in Example 1 and the uranium adsorption electrode prepared in Example 12 were subjected to a uranium adsorption experiment in real seawater to determine their adsorption effects on hexavalent uranium. The steps were to determine the uranium adsorption of the two materials in 25L real seawater for 24 hours. The results are shown in Figure 2. Fig.10 shown.
[0128] Fig.10 is a comparison diagram of the adsorption effect of Example 1 and Example 12 on hexavalent uranium, Fig.10It can be seen that the electric field-assisted uranium adsorption composite material prepared by the present invention can regulate the adsorption effect on hexavalent uranium under an external electric field.
[0129] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing an electric field-assisted uranium adsorption composite material, characterized in that the steps include: A metal ion-containing salt and an organic ligand are used as reactants, and a MOFs material containing a cyano group is obtained through a solvent thermal reaction; the organic ligand is terephthalic acid and 2,5-dicyanoterephthalic acid; Graphene oxide and carboxylated cellulose nanofibers are used as reactants, ethylenediamine is used as a cross-linking agent, and a graphene aerogel is obtained through a hydrothermal reaction. The MOFs material containing cyano groups and the graphene aerogel are mixed and loaded in a solvent, and then dried to obtain the electric field assisted uranium adsorption composite material; The molar ratio of the metal ion to the organic ligand in the metal ion-containing salt is 1:1-10; the molar ratio of terephthalic acid to 2,5-dicyanoterephthalic acid is 1:0.2-5; the metal ion in the metal ion-containing salt includes Zr 4+ , Fe 3+ , Cu 2+ and Zn 2+ At least one of the following; the temperature of the solvent thermal reaction is 120°C and the time is 12 to 48 hours; The mass ratio of the graphene oxide to the carboxylated cellulose nanofibers is 1:0.1-1; the mass / volume ratio of the sum of the mass of the graphene oxide and the carboxylated cellulose nanofibers to ethylenediamine is 0.055-0.1 g:2 μL; the temperature of the hydrothermal reaction is 120° C., and the time is 8-12 hours; The mass ratio of the MOFs material containing cyano groups to the graphene aerogel is 1:1-12.5; the time of the mixing reaction is 24-48 hours, and the temperature is room temperature; and the solvent is N,N-dimethylformamide.
2. An electric field assisted uranium adsorption composite material prepared by the preparation method as claimed in claim 1.
3. Use of the electric field assisted uranium adsorption composite material as claimed in claim 2 in uranium adsorption.
4. A uranium adsorption electrode, characterized in that: The raw material includes the electric field assisted uranium adsorption composite material as described in claim 2.
5. A method for preparing a uranium adsorption electrode as claimed in claim 4, characterized in that the steps include: The electric field assisted uranium adsorption composite material is dispersed in an ethanol solution, and then naphthol is added, mixed evenly, and then coated on a conductive substrate to obtain the uranium adsorption electrode.
6. The preparation method according to claim 5, characterized in that: The mass fraction of the ethanol solution is 75-95%; the volume ratio of the ethanol solution to naphthol is 40-80:1; the content of the electric field-assisted uranium adsorption composite material in the mixed system is 0.2-1g:50mL; the conductive substrate is carbon paper, carbon cloth or graphite felt; the loading amount of the electric field-assisted uranium adsorption composite material in the uranium adsorption electrode is 0.2-2mg / cm 2 .
7. Use of the uranium adsorption electrode as claimed in claim 4 as an adsorption material in electrosorption enrichment of uranium.
Citation Information
Patent Citations
Modified diaminooxime UiO-66-2AO material, preparation method and application of modified diaminooxime UiO-66-2AO material in adsorption of uranyl ions in water
CN115672279A